(untitled) (San Prancisco, CA., 2007)
The Ministers Manual is focused upon the day-to-day work of the pastor. It concentrates upon the art of sermon building, biblical exegesis, and multiple aspects of human need in life situations. It is an invaluable handbook . . ."
Keywords: Diplomats,Ngoại giao; Minister,Manual,Cấp bộ trưởng